Effect of Shea Nutshell Ash on the Mechanical Properties of Cast Al6061 - Zubairu, P. T.; Hassan, A. B.; Muriana, R. A.; Musa, N. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
Aluminium Matrix Composites (AMCs) has attracted much interest in aerospace, defence and automotive applications due to its high strength to weight ratio. However, the manufacturing technique, nature and combination of the matrix and reinforcements play a vital role in the success of AMCs. In this study, the mechanical properties of Aluminium metal matrix composites (AMMCs) reinforced with shea nutshell ash (SSA) was investigated. Different mix ratio constituting 0%, 5%, and 10% of SSA were used as reinforcement, with the matrix being Al6061 to compound different samples. The metal matrix composites were produced by stir casting technique. Mechanical properties such as Hardness, Tensile, Impact and Microstructure examination of the developed composites were evaluated. The results showed that with increasing % of SSA, the hardness, and impact energy of the composite increased for both 5 and 10%. However, with increasing SSA the tensile strength decreased slightly for both 5 and 10% SSA. The hardness and the impact energy increased by 166.74% and 76.38% respectively as the wt% of SSA varied from 0-10tw%. On the other hand, the tensile test showed a decrease from 115.67 N/mm2 to 94.52 N/mm2 as the % of SSA increase from 0-10%; which translates to 18.29% reduction in tensile strength. SSA however promises to be a good reinforcement material for hybrid aluminium matrix composites when the properties desired are hardness and impact energy.